POLA INTERAKSI DALAM RUANG VIRTUAL (STUDI DESKRIPTIF KUALITATIF KOMUNIKASI VIRTUAL ANTARA STREAMER VALORANT DAN PENONTON PADA CHANNEL YOUTUBE XCCURATE) - Triandika Hartadia Saputra; Haryo Kusumo Aji (Solidaritas, 2025)
The phenomenon of game Live Streaming on YouTube presents a unique pattern of virtual communication between streamers and viewers. This study aims to describe the interaction patterns between the streamer Xccurate and viewers during the Live Streaming of the game VALORANT, as well as the role of interactive features in fostering audience engagement. Using a descriptive qualitative method, data were collected through digital observation, structured interviews, and documentation, with data validity tested using the triangulation technique. The theories applied include Virtual Communication, Interactive Communication, and Interaction Patterns (synchronous, asynchronous, one-to-one, one-to-many, many-to-many). The results show that the interaction pattern is dominated by synchronous communication via live chat, with one-to-many as the primary pattern, followed by one-to-one and many-to-many. Features such as Super Chat, emojis, membership stickers, and polling strengthen participation, while moderators maintain the quality of conversation. The combination of a relaxed communication style and the use of interactive features results in dynamic, participatory, and multidirectional interactions. Keywords : virtual communication, interaction pattern, Live Streaming, VALORANT, YouTube